PENURUNAN PEROLEHAN SUARA PARTAI GERAKAN INDONESIA RAYA (GERINDRA) PADA PEMILIHAN UMUM DI KABUPATEN ROKAN HULU TAHUN 2024 - Azhari, Ragil; ,, Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Rokan Hulu Regency Branch Leadership Council (DPC) of the Gerindra Party was the party with the highest number of votes in the 2019 election. However, in the 2024 election, the Gerindra Party experienced a significant decline in votes, falling to fourth place. This research discusses the vote acquisition of the Gerindra Party in the election for the Regional House of Representatives (DPRD) of Rokan Hulu Regency in 2024. It explains the factors behind the decline in Gerindra’s vote share, which dropped from 17.26% in the 2019 election to 12.01% in the 2024 election. This study uses a qualitative method through descriptive analysis to illustrate the distribution and factors contributing to the decline in Gerindra Party’s vote acquisition in Rokan Hulu Regency in 2024. Data collection techniques included interviews as primary data, and mass media and documentation as secondary data. The theoretical framework used includes leadership theory by Vietzal Rivai and party institutionalization theory by Basedau and Stroh. Based on the research findings, the decline in Gerindra’s vote share occurred across five out of the six electoral districts (dapils) in Rokan Hulu Regency, meaning that only one dapil managed to increase its vote share compared to the previous election. The factors causing the decline include issues related to party institutionalization, which can be broken down into four elements: the party's weak grassroots presence in society, its inability to operate autonomously and resist external influences, disruption in the party’s organizational strength due to two leadership changes within the DPC Gerindra, and a lack of internal coherence caused by internal divisions resulting from the dual leadership changes. Keywords: Political Party, Gerindra Party, Election, Decline in vote